An Investigation on Inclusions Forming During Remelting of Aluminum and Magnesium Scraps Under a Salt Flux - Gökelma, Mertol; Çapkın, İrem Yaren; Gökelma, Mertol (Springer, 2023)
Due to increasing environmental and economic concerns, the recycling of metals has been increasing in the last decades. Aluminum saves up to 95% of energy when recycled, and magnesium is one of the most common alloying elements in aluminum alloys, contributing to oxidation behavior. Both aluminum and magnesium have a high oxidation tendency during remelting, which raises the necessity for salt flux usage. Salt fluxes remove oxides and other surface contaminants from the target metal. Salt fluxes allow molten metal pieces to coagulate and form the molten bath. Furthermore, it prevents further oxidation of the metal. The presence of fluorides increases the metal yield by promoting coalescence. Although metals and salts are frequently interacting in such processes, there is still a lack of knowledge of the final and intermediate products of the interaction reactions. This study aims to contribute to the literature by investigating the interaction of aluminum and magnesium scraps with salt flux. As a result of the experiments, AlF3, MgF2, Al2O3, MgO, and MgAl2O4 were observed as the main phases in the aluminum and magnesium scraps dross. The presence of CaF2 in the salt flux, which is insoluble in water, was also observed in the analysis results. In addition, fluorine-containing compounds were observed as a result of chemical interactions among the F-, K-, and oxide layers.
Article; Early Access